2015
DOI: 10.3141/2489-17
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Adaptive Cruise Control

Abstract: Cooperative adaptive cruise control (CACC) includes multiple concepts of communication-enabled vehicle following and speed control. Definitions and classifications are presented to help clarify the distinctions between types of automated vehicle-following control that are often conflated with each other. A distinction is made between vehicle-to-vehicle (V2V) CACC, based on vehicle–vehicle cooperation, and infrastructure-to-vehicle CACC, in which the infrastructure provides information or guidance to the CACC s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(59 citation statements)
references
References 15 publications
0
58
0
1
Order By: Relevance
“…At this point, the particle has two degrees of freedom in the plane, including the longitudinal direction and lateral direction. Since the acceleration of the vehicle is limited by road adhesion, the control variable u(t) of the vehicle particle dynamics model is selected as acceleration, and the particle dynamics model can be simplified, as shown in formula (1), where x G and v G are 2-D vectors.…”
Section: Particle Dynamic Model and Reference Vector Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…At this point, the particle has two degrees of freedom in the plane, including the longitudinal direction and lateral direction. Since the acceleration of the vehicle is limited by road adhesion, the control variable u(t) of the vehicle particle dynamics model is selected as acceleration, and the particle dynamics model can be simplified, as shown in formula (1), where x G and v G are 2-D vectors.…”
Section: Particle Dynamic Model and Reference Vector Fieldmentioning
confidence: 99%
“…Vehicle platoon enables multiple vehicles to drive in a formation by automatically adjusting the spacing between the cars. By maintaining a reasonable distance and yaw angle between the adjacent cars, the "traction effect" in aerodynamics can effectively save energy and reduce pollutant emissions [1]. Besides, platoon control can increase traffic capacity and reduce the probability of traffic accidents, which was demonstrated in many studies [2][3][4].…”
Section: Introductionmentioning
confidence: 98%
“…Automated driving systems have attracted considerable attention in the recent years, because of the fundamental changes they bring to transportation systems and new services enabled by them. Literature has shown that the individual automation can hardly enhance traffic operations while it is commonly agreed that connected/cooperative automated vehicles (CAVs) possess great potential in increasing roadway capacity and traffic flow stability [13,21,23,24,28]. Vehicle platooning is one of multiple applications that stands out in the domain, characterized by a string of CAVs respecting a specified equilibrium spacing policy [3,15,22,24].…”
Section: Introductionmentioning
confidence: 99%
“…Also, ACC systems, like traditional human driving, may not exhibit string instability, i.e., due to higher response time, fluctuations in traffic flow induced by accelerating and braking of vehicles can be amplified upstream, resulting in phantom traffic jams. CACC systems, on the other hand, have been shown to overcome this limitation by adding V2V communication to ACC (Shladover, Nowakowski, Lu, & Ferlis, 2015;Milanés et al, 2014). Thus, CACC equipped vehicles can get information from similarly equipped vehicles ahead of them downstream and use this information to make decisions related to their own speed and acceleration.…”
Section: Introduction To Cacc Platoonsmentioning
confidence: 99%